Early-onset severe neuromatous pain of the infrapatellar branch of the saphenous nerve after total knee arthroplasty - Kanto Nagai; Hirotsugu Muratsu; Tomoyuki Matsumoto; Isao Fujibayashi; Ryosuke Kuroda; Masahiro Kurosaka (Elsevier, 2014)
While performing total knee arthroplasty (TKA) using a standard midline skin incision, the transection of the infrapatellar branch of the saphenous nerve (ISN) or its terminal branches is relatively common. This usually causes an area of numbness in the distribution of the ISN, but rarely results in painful neuroma. Usually, the progress of neuromatous pain is relatively slow and the degree of the pain is not so severe, but in our present case the progress of neuromatous pain was rapid and severe, and therefore, the patient could not be discharged from our hospital after TKA. To our knowledge, there has been no previous report demonstrating early-onset neuromatous knee pain after TKA in the English literature. We present a rare case in which early-onset severe neuromatous pain was encountered after TKA and partial denervation of the ISN was effective. Neuromatous knee pain can occur shortly after TKA, and, in these cases, surgeons should consider partial denervation for patients who have intractable neuromatous pain before functional loss occurs.